Follicular Helper T-Cell–derived Nodal Lymphomas: Study of Histomorphologic, Immunophenotypic, Clinical, and RHOA G17V Mutational Profile. Issue 3 (20th March 2023) - Jain, Surabhi; Goswami, Ansh; Lone, Moien R.; Ramteke, Prashant; Gogia, Ajay; Aggarwal, Mukul; Viswanathan, Ganesh K.; Kakkar, Disha; Mandal, Trisha; Sharma, Atul; Sahoo, Ranjit; Baldia, Anshu; et al.
Abstract : The study was designed to review the demographic, clinical, and pathologic characteristics of follicular helper T cells (TFH)-derived nodal PTCL in India including angioimmunoblastic T-cell lymphoma (AITL), peripheral T-cell lymphoma (PTCL) with follicular helper T cell phenotype (P-TFH), and follicular T-cell lymphoma with additional immunohistochemistry (IHC) and RHOAG17V mutational analysis, as well as their impact on survival. This retrospective study included 88 cases of PTCL that were reclassified using IHC for TFH markers (PD1, ICOS, BCL6, and CD10) and dendritic-meshwork markers (CD21, CD23). Cases of TFH cell origin were evaluated for RHOAG17V mutation using Sanger sequencing and amplification-refractory mutation system–polymerase chain reaction (PCR) (validated using cloning and quantitative PCR) with detailed clinicopathologic correlation. Extensive re-evaluation with added IHC panel resulted in a total of 19 cases being reclassified, and the final subtypes were AITL (37 cases, 42%), PTCL—not otherwise specified (44, 50%), P-TFH (6, 7%), and follicular T-cell lymphoma (1, 1%). The presence of at least 2 TFH markers (>20% immunopositivity) determined the TFH origin. AITL patients tended to be male and showed increased presence of B-symptoms and hepatosplenomegaly. Histomorphology revealed that 92% of AITL cases had pattern 3 involvement. Sanger sequencing with conventional PCR did not yield any mutation, while RHOAG17V was detected by amplification-refractory mutation system–PCR in AITL (51%, P =0.027) and P-TFH (17%), which was validated with cloning followed by sequencing. Cases of RHOAG17V-mutant AITL had a worse Eastern Cooperative Oncology Group performance status initially but fared better in terms of overall outcome ( P =0.029). Although not specific for AITL, RHOAG17V mutation shows an association with diagnosis and requires sensitive methods for detection due to low-tumor burden. The mutant status of AITL could have prognostic implications and translational relevance.